The Role of Information Technology in Advancing Education in the 21st Century - Novita, Novita; Sandra Dwi Hidayani; Ekariawati (Jurnal Pendidikan Vokasi Indonesia, 2022)
The purpose of writing this article is to describe the role of information technology in education. Through education, especially for facilitators in the form of teachers, of course, they are given more burdens and obligations to carry out teaching and learning activities along with following increasingly rapid technological developments so that they are not left far behind. Especially at this time, the prospective young generation in the form of students is no strangers to using and accessing technological facilities that are very developed at this time. This type of research is a literature review. The literature review is a method used to describe a finding or theory as further research material that is obtained and used as a reference or basis for an activity in the preparation of a framework of thinking and also taken from the formulation of relevant problems. This method is quite systematic and explicit because it is carried out by identifying, evaluating, and synthesizing a work of research results and ideas that have been previously carried out by researchers and practitioners. In line with advances in information technology, many activities can be carried out using information technology networks. Information technology can be used as a good source of learning because information technology can access various learning resources in the form of writing, images, videos, sounds, and software, all of which can be downloaded and stored so that distance learning is also possible.